2016
DOI: 10.21697/zp.2015.15.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Stan Nietrzeźwości Jako „afekt” W Rzymskim Prawie Karnym?

Abstract: Drunkenness – a “Passion” in Roman Criminal Law?SummarySince ancient times jurists and lawyers have had to handle offencesconnected with alcohol abuse. There are only three texts on drunkenness in the Roman legal sources: two relate to offences committed byinebriate soldiers, and the third contains the basic division into intentional offences, accidental offences, and crimes of passion. In all threecategories drunkenness was a mitigating factor, which may be surprising for modern lawyers. Other Roman sources p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…An extensive photometric study of the system was presented by Goossens et al (1984) based on the observations collected by Van Hoof (1966) in the ultraviolet (UV), yellow (Y), and blue (B) light. The authors reported on the light variability in all three pass-bands with the same two dominant modes as found by Kubiak & Seggewiss (1983). On the other hand, the colour variations revealed only one dominant frequency f 1 =4.05118 d −1 (46.87215 µHz).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…An extensive photometric study of the system was presented by Goossens et al (1984) based on the observations collected by Van Hoof (1966) in the ultraviolet (UV), yellow (Y), and blue (B) light. The authors reported on the light variability in all three pass-bands with the same two dominant modes as found by Kubiak & Seggewiss (1983). On the other hand, the colour variations revealed only one dominant frequency f 1 =4.05118 d −1 (46.87215 µHz).…”
Section: Introductionsupporting
confidence: 61%
“…Two out of the eight frequencies, the dominant mode f 1 =4.05111 d −1 (46.87132 µHz) and f 2 =4.17588 d −1 (48.31495 µHz), were found to be independent modes whereas the other six frequencies appeared as their low-order combination terms (including harmonics). Based on the analysis of both photoelectric (taken in ubvy Stromgren system) and spectroscopic data, Kubiak & Seggewiss (1983) found non-radial pulsations to be the most reasonable explanation of the observed variability.…”
Section: Introductionmentioning
confidence: 94%